Identification and Computational Analysis of Novel TYR and SLC45A2 Gene Mutations in Pakistani Families With Identical Non-syndromic Oculocutaneous Albinism - Bibi, Nousheen; Ullah, Asmat; Darwesh, Lubna; Khan, Waqas; Khan, Tanzeela; Ullah, Kalim; Khan, Bushra; Ahmad, Wasim; , Umm-e-Kalsoom (Frontiers in Genetics, 2020)
Non syndromic Oculocutaneous Albinisim (nsOCA) is an inherited disorder of melanin biosynthesis with autosomal recessive mode of inheritance, presenting either hypo pigmented or depigmented skin, hairs, and eyes. It is genetically heterogeneous with seven loci (OCA1-OCA7) reported to date. In the present study, we have reported three consanguineous families (A, B, C) presenting identical nsOCA phenotypes. Sanger sequencing revealed a novel [NM_000372.5: c.826 T>C, p.(Cys276Arg)] and a recurrent variant [NM_000372.5: c.832C>T, p. (Arg278*)] in Tyrosinase (TYR) in family A and B, respectively. Microsatellite markers-based homozygosity mapping linked family C to OCA4. Sequence analysis identified a novel insertion variant (NM_016180.5: c.1331_1332insA) in the SLC45A2. Further, in-silico mutagenesis and dynamic simulation approaches revealed that a novel Cys276Arg variant abolished the cysteine bridge and might contribute towards decrease stability of the TYR protein. Our study expands the mutation spectrum of the TYR and SLC45A2 genes and emphasizes that molecular investigations are essential for accurate disease diagnosis.